Effects of surface instability on cortical information processing during multi- joint compound movements: an exploratory EEG study - Lehmann, Tim; Visser, Anton; Havers, Tim; Büchel, Daniel; Baumeister, Jochen

Performance and Brain Activity in Older Adults while Playing Leaning and Stepping Exergames - Müller, Helen Martha; Skjæret-Maroni, Nina; Vereijken, Beatrix; Baumeister, Jochen

Changes In Eeg Microstate Patterns Following Exhaustive Treadmill Exercise When Employing Reduced Channel Resolution - Büchel, Daniel; Allen, Carlos; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Medicine & Science in Sports & Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Ecological validity in exercise neuroscience research: A systematic investigation - Chang, Melissa; Büchel, Daniel; Reinecke, Kirsten; Lehmann, Tim; Baumeister, Jochen (European Journal of Neuroscience)
Keywords: General Neuroscience

Have We Forgotten Our Patient? An Exploration of Patient Experiences After Anterior Cruciate Ligament Reconstruction - Welling, Wouter; Gokeler, Alli; Benjaminse, Anne; Verhagen, Evert; Lemmink, Koen (Journal of Sport Rehabilitation)
Background: Limited information is available on the experiences of patients during rehabilitation after anterior cruciate ligament reconstruction (ACLR). Aim: The current study aimed to identify factors that differentiated positive and negative patient experiences during rehabilitation after ACLR. Method and Design: A survey-based study with an online platform was used to identify factors that differentiated positive and negative patient experiences during rehabilitation after ACLR. Seventy-two patients (age 27.8 [8.8] y) after ACLR participated. Data were analyzed and themes were identified by comparing categories and subcategories on similarity. Main Findings: Positive patient experiences were room for own input, supervision, attention, knowledge, honesty, and professionalism of the physiotherapist. Additionally, a varied and structured rehabilitation program, adequate facilities, and contact with other patients were identified as positive patient experiences. Negative experiences were a lack of attention, lack of professionalism of the physiotherapists, a lack of sport-specific field training, a lack of goal setting, a lack of adequate facilities, and health insurance costs. Conclusions: The current study identified factors that differentiated positive and negative patient experiences during rehabilitation after ACLR. These findings can help physiotherapists in understanding the patient experiences during rehabilitation after ACLR.

Rehabilitation and Return to Sport Testing After Anterior Cruciate Ligament Reconstruction: Where Are We in 2022? - Gokeler, Alli; Dingenen, Bart; Hewett, Timothy E. (Arthroscopy, Sports Medicine, and Rehabilitation)

Changes In Eeg Microstate Patterns Following Exhaustive Treadmill Exercise When Employing Reduced Channel Resolution - Büchel, Daniel; Allen, Carlos; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Medicine &Science in Sports& Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Exploring intensity-dependent modulations in EEG resting-state network efficiency induced by exercise - Büchel, Daniel; Sandbakk, Øyvind; Baumeister, Jochen (European Journal of Applied Physiology)
Abstract Purpose Exhaustive cardiovascular load can affect neural processing and is associated with decreases in sensorimotor performance. The purpose of this study was to explore intensity-dependent modulations in brain network efficiency in response to treadmill running assessed from resting-state electroencephalography (EEG) measures. Methods Sixteen trained participants were tested for individual peak oxygen uptake (VO 2 peak ) and performed an incremental treadmill exercise at 50% (10 min), 70% (10 min) and 90% speed VO 2 peak (all-out) followed by cool-down running and active recovery. Before the experiment and after each stage, borg scale (BS), blood lactate concentration (B La ), resting heartrate (HR rest ) and 64-channel EEG resting state were assessed. To analyze network efficiency, graph theory was applied to derive small world index (SWI) from EEG data in theta, alpha-1 and alpha-2 frequency bands. Results Analysis of variance for repeated measures revealed significant main effects for intensity on BS, B La , HR rest and SWI. While BS, B La and HR rest indicated maxima after all-out, SWI showed a reduction in the theta network after all-out. Conclusion Our explorative approach suggests intensity-dependent modulations of resting-state brain networks, since exhaustive exercise temporarily reduces brain network efficiency. Resting-state network assessment may prospectively play a role in training monitoring by displaying the readiness and efficiency of the central nervous system in different training situations.

Stance leg and surface stability modulate cortical activity during human single leg stance - Büchel, Daniel; Lehmann, Tim; Ullrich, Sarah; Cockcroft, John; Louw, Quinette; Baumeister, Jochen (Experimental Brain Research)
Abstract Mobile Electroencephalography (EEG) provides insights into cortical contributions to postural control. Although changes in theta (4–8 Hz) and alpha frequency power (8–12 Hz) were shown to reflect attentional and sensorimotor processing during balance tasks, information about the effect of stance leg on cortical processing related to postural control is lacking. Therefore, the aim was to examine patterns of cortical activity during single-leg stance with varying surface stability. EEG and force plate data from 21 healthy males (22.43 ± 2.23 years) was recorded during unipedal stance (left/right) on a stable and unstable surface. Using source-space analysis, power spectral density was analyzed in the theta, alpha-1 (8–10 Hz) and alpha-2 (10–12 Hz) frequency bands. Repeated measures ANOVA with the factors leg and surface stability revealed significant interaction effects in the left ( p = 0.045, η p 2 = 0.13) and right motor clusters ( F = 16.156; p = 0.001, η p 2 = 0.41). Furthermore, significant main effects for surface stability were observed for the fronto-central cluster (theta), left and right motor (alpha-1), as well as for the right parieto-occipital cluster (alpha-1/alpha-2). Leg dependent changes in alpha-2 power may indicate lateralized patterns of cortical processing in motor areas during single-leg stance. Future studies may therefore consider lateralized patterns of cortical activity for the interpretation of postural deficiencies in unilateral lower limb injuries.

Functional Cortical Connectivity Related to Postural Control in Patients Six Weeks After Anterior Cruciate Ligament Reconstruction - Lehmann, Tim; Büchel, Daniel; Mouton, Caroline; Gokeler, Alli; Seil, Romain; Baumeister, Jochen (Frontiers in Human Neuroscience)
Whereas initial findings have already identified cortical patterns accompanying proprioceptive deficiencies in patients after anterior cruciate ligament reconstruction (ACLR), little is known about compensatory sensorimotor mechanisms for re-establishing postural control. Therefore, the aim of the present study was to explore leg dependent patterns of cortical contributions to postural control in patients 6 weeks following ACLR. A total of 12 patients after ACLR (25.1 ± 3.2 years, 178.1 ± 9.7 cm, 77.5 ± 14.4 kg) and another 12 gender, age, and activity matched healthy controls participated in this study. All subjects performed 10 × 30 s. single leg stances on each leg, equipped with 64-channel mobile electroencephalography (EEG). Postural stability was quantified by area of sway and sway velocity. Estimations of the weighted phase lag index were conducted as a cortical measure of functional connectivity. The findings showed significant group × leg interactions for increased functional connectivity in the anterior cruciate ligament (ACL) injured leg, predominantly including fronto−parietal [ F (1, 22) = 8.41, p ≤ 0.008, η 2 = 0.28], fronto−occipital [ F (1, 22) = 4.43, p ≤ 0.047, η 2 = 0.17], parieto−motor [ F (1, 22) = 10.30, p ≤ 0.004, η 2 = 0.32], occipito−motor [ F (1, 22) = 5.21, p ≤ 0.032, η 2 = 0.19], and occipito−parietal [ F (1, 22) = 4.60, p ≤ 0.043, η 2 = 0.17] intra−hemispherical connections in the contralateral hemisphere and occipito−motor [ F (1, 22) = 7.33, p ≤ 0.013, η 2 = 0.25] on the ipsilateral hemisphere to the injured leg. Higher functional connectivity in patients after ACLR, attained by increased emphasis of functional connections incorporating the somatosensory and visual areas, may serve as a compensatory mechanism to control postural stability of the injured leg in the early phase of rehabilitation. These preliminary results may help to develop new neurophysiological assessments for detecting functional deficiencies after ACLR in the future.

EEG-derived brain graphs are reliable measures for exploring exercise-induced changes in brain networks - Büchel, Daniel; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Scientific Reports)
Abstract The interaction of acute exercise and the central nervous system evokes increasing interest in interdisciplinary research fields of neuroscience. Novel approaches allow to monitor large-scale brain networks from mobile electroencephalography (EEG) applying graph theory, but it is yet uncertain whether brain graphs extracted after exercise are reliable. We therefore aimed to investigate brain graph reliability extracted from resting state EEG data before and after submaximal exercise twice within one week in male participants. To obtain graph measures, we extracted global small-world-index (SWI), clustering coefficient (CC) and characteristic path length (PL) based on weighted phase leg index (wPLI) and spectral coherence (Coh) calculation. For reliability analysis, Intraclass-Correlation-Coefficient (ICC) and Coefficient of Variation (CoV) were computed for graph measures before (REST) and after POST) exercise. Overall results revealed poor to excellent measures at PRE and good to excellent ICCs at POST in the theta, alpha-1 and alpha-2, beta-1 and beta-2 frequency band. Based on bootstrap-analysis, a positive effect of exercise on reliability of wPLI based measures was observed, while exercise induced a negative effect on reliability of Coh-based graph measures. Findings indicate that brain graphs are a reliable tool to analyze brain networks in exercise contexts, which might be related to the neuroregulating effect of exercise inducing functional connections within the connectome. Relative and absolute reliability demonstrated good to excellent reliability after exercise. Chosen graph measures may not only allow analysis of acute, but also longitudinal studies in exercise-scientific contexts.

Stance leg and surface stability modulate cortical activity during human single leg stance - Büchel, Daniel; Lehmann, Tim; Ullrich, Sarah; Cockcroft, John; Louw, Quinette; Baumeister, Jochen (Experimental Brain Research)

Neurocognitive and Neurophysiological Functions Related to ACL Injury: A Framework for Neurocognitive Approaches in Rehabilitation and Return-to-Sports Tests - Piskin, Daghan Yuksel; Benjaminse, Anne; Dimitrakis, Panagiotis; Gokeler, Alli (Sports Health: A Multidisciplinary Approach)
Context: Only 55% of the athletes return to competitive sports after an anterior cruciate ligament (ACL) injury. Athletes younger than 25 years who return to sports have a second injury rate of 23%. There may be a mismatch between rehabilitation contents and the demands an athlete faces after returning to sports. Current return-to-sports (RTS) tests utilize closed and predictable motor skills; however, demands on the field are different. Neurocognitive functions are essential to manage dynamic sport situations and may fluctuate after peripheral injuries. Most RTS and rehabilitation paradigms appear to lack this aspect, which might be linked to increased risk of second injury. Objective: This systematic and scoping review aims to map existing evidence about neurocognitive and neurophysiological functions in athletes, which could be linked to ACL injury in an integrated fashion and bring an extensive perspective to assessment and rehabilitation approaches. Data Sources: PubMed and Cochrane databases were searched to identify relevant studies published between 2005 and 2020 using the keywords ACL, brain, cortical, neuroplasticity, cognitive, cognition, neurocognition, and athletes. Study Selection: Studies investigating either neurocognitive or neurophysiological functions in athletes and linking these to ACL injury regardless of their design and technique were included. Study Design: Systematic review. Level of Evidence: Level 3. Data Extraction: The demographic, temporal, neurological, and behavioral data revealing possible injury-related aspects were extracted and summarized. Results: A total of 16 studies were included in this review. Deficits in different neurocognitive domains and changes in neurophysiological functions could be a predisposing risk factor for, or a consequence caused by, ACL injuries. Conclusion: Clinicians should view ACL injuries not only as a musculoskeletal but also as a neural lesion with neurocognitive and neurophysiological aspects. Rehabilitation and RTS paradigms should consider these changes for assessment and interventions after injury.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

PIVOT: A Parsimonious End-to-End Learning Framework for Valuing Player Actions in Handball using Tracking Data - Müller, Oliver; Caron, Matthew; Döring, Michael; Heuwinkel, Tim; Baumeister, Jochen (8th Workshop on Machine Learning and Data Mining for Sports Analytics (ECML PKDD 2021))
Over the last years, several approaches for the data-driven estimation of expected possession value (EPV) in basketball and association football (soccer) have been proposed. In this paper, we develop and evaluate PIVOT: the first such framework for team handball. Accounting for the fast-paced, dynamic nature and relative data scarcity of hand- ball, we propose a parsimonious end-to-end deep learning architecture that relies solely on tracking data. This efficient approach is capable of predicting the probability that a team will score within the near future given the fine-grained spatio-temporal distribution of all players and the ball over the last seconds of the game. Our experiments indicate that PIVOT is able to produce accurate and calibrated probability estimates, even when trained on a relatively small dataset. We also showcase two interactive applications of PIVOT for valuing actual and counterfactual player decisions and actions in real-time.
Keywords: expected possession value; handball; tracking data; time series classification; deep learning

Somatosensory perturbations influence cortical activity associated with single-limb balance performance - Sherman, David A.; Lehmann, Tim; Baumeister, Jochen; Grooms, Dustin R.; Norte, Grant E. (Experimental Brain Research)
Keywords: General Neuroscience

External Focus of Attention Influences Cortical Activity Associated with Single Limb Balance Performance - Sherman, David A; Lehmann, Tim; Baumeister, Jochen; Gokeler, Alli; Donovan, Luke; Norte, Grant E (Physical Therapy)
Abstract Objective External focus (EF) of attention leads to improved balance performance. Consideration of the neuromodulatory effects of EF may inform its clinical utility in addressing neuroplastic impairments after musculoskeletal injuries. We aimed to determine whether electrocortical activity and balance performance changed with attentional foci that prioritized differing sensory feedback and whether changes in electrocortical activity and balance were associated. Methods Individuals who were healthy (n = 15) performed a single-limb balance task under 3 conditions: internal focus (IF), somatosensory focus [EF with a baton (EF-baton)], and visual focus [EF with a laser (EF-laser)]. Electrocortical activity and postural sway were recorded concurrently using electroencephalography and a triaxial force plate. Electroencephalographic signals were decomposed, localized, and clustered to generate power spectral density in θ and α-2 frequency bands. Postural sway signals were analyzed with center-of-pressure sway metrics (eg, area, distance, velocity) and knee angle. The relationship between percent change in clustered brain activity and task performance metrics was assessed. Results Both EF conditions resulted in increased cortical activity and improved balance performance compared to IF. EF-laser had the largest effect, demonstrating increased frontal θ power (d = 0.64), decreased central θ power (d = −0.30), and decreased bilateral motor, bilateral parietal, and occipital α-2 power (d = −1.38 to −4.27) as well as a shorter path distance (d = −0.94) and a deeper (d = 0.70) and less variable (d = −1.15) knee angle than IF. Weak to moderate associations exist between increases in cortical activity and improved balance performance (ρ = 0.405–0.584). Conclusions EF resulted in increased cortical activity associated with cognitive, motor, somatosensory, and visual processing. EF-laser, which prioritized visual feedback, had the largest and broadest effects. Changes in cortical activity resulting from EF were independently associated with improved balance performance. Impact This study demonstrates that goal-oriented attention results in functional increases in brain activity compared to internally directed self-focus. These results suggest EF may target neurophysiologic impairments and improve balance in clinical populations.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation

Functional Cortical Connectivity Related to Postural Control in Patients Six Weeks After Anterior Cruciate Ligament Reconstruction - Lehmann, Tim; Büchel, Daniel; Mouton, Caroline; Gokeler, Alli; Seil, Romain; Baumeister, Jochen (Frontiers in Human Neuroscience)
Whereas initial findings have already identified cortical patterns accompanying proprioceptive deficiencies in patients after anterior cruciate ligament reconstruction (ACLR), little is known about compensatory sensorimotor mechanisms for re-establishing postural control. Therefore, the aim of the present study was to explore leg dependent patterns of cortical contributions to postural control in patients 6 weeks following ACLR. A total of 12 patients after ACLR (25.1 ± 3.2 years, 178.1 ± 9.7 cm, 77.5 ± 14.4 kg) and another 12 gender, age, and activity matched healthy controls participated in this study. All subjects performed 10 × 30 s. single leg stances on each leg, equipped with 64-channel mobile electroencephalography (EEG). Postural stability was quantified by area of sway and sway velocity. Estimations of the weighted phase lag index were conducted as a cortical measure of functional connectivity. The findings showed significant group × leg interactions for increased functional connectivity in the anterior cruciate ligament (ACL) injured leg, predominantly including fronto−parietal [ F (1, 22) = 8.41, p ≤ 0.008, η 2 = 0.28], fronto−occipital [ F (1, 22) = 4.43, p ≤ 0.047, η 2 = 0.17], parieto−motor [ F (1, 22) = 10.30, p ≤ 0.004, η 2 = 0.32], occipito−motor [ F (1, 22) = 5.21, p ≤ 0.032, η 2 = 0.19], and occipito−parietal [ F (1, 22) = 4.60, p ≤ 0.043, η 2 = 0.17] intra−hemispherical connections in the contralateral hemisphere and occipito−motor [ F (1, 22) = 7.33, p ≤ 0.013, η 2 = 0.25] on the ipsilateral hemisphere to the injured leg. Higher functional connectivity in patients after ACLR, attained by increased emphasis of functional connections incorporating the somatosensory and visual areas, may serve as a compensatory mechanism to control postural stability of the injured leg in the early phase of rehabilitation. These preliminary results may help to develop new neurophysiological assessments for detecting functional deficiencies after ACLR in the future.
Keywords: Behavioral Neuroscience; Biological Psychiatry; Psychiatry and Mental health; Neurology; Neuropsychology and Physiological Psychology

Stance leg and surface stability modulate cortical activity during human single leg stance - Büchel, Daniel; Lehmann, Tim; Ullrich, Sarah; Cockcroft, John; Louw, Quinette; Baumeister, Jochen (Experimental Brain Research)
Abstract Mobile Electroencephalography (EEG) provides insights into cortical contributions to postural control. Although changes in theta (4–8 Hz) and alpha frequency power (8–12 Hz) were shown to reflect attentional and sensorimotor processing during balance tasks, information about the effect of stance leg on cortical processing related to postural control is lacking. Therefore, the aim was to examine patterns of cortical activity during single-leg stance with varying surface stability. EEG and force plate data from 21 healthy males (22.43 ± 2.23 years) was recorded during unipedal stance (left/right) on a stable and unstable surface. Using source-space analysis, power spectral density was analyzed in the theta, alpha-1 (8–10 Hz) and alpha-2 (10–12 Hz) frequency bands. Repeated measures ANOVA with the factors leg and surface stability revealed significant interaction effects in the left ( p = 0.045, η p 2 = 0.13) and right motor clusters ( F = 16.156; p = 0.001, η p 2 = 0.41). Furthermore, significant main effects for surface stability were observed for the fronto-central cluster (theta), left and right motor (alpha-1), as well as for the right parieto-occipital cluster (alpha-1/alpha-2). Leg dependent changes in alpha-2 power may indicate lateralized patterns of cortical processing in motor areas during single-leg stance. Future studies may therefore consider lateralized patterns of cortical activity for the interpretation of postural deficiencies in unilateral lower limb injuries.
Keywords: General Neuroscience

EEG‑derived brain graphs are reliable measures for exploring exercise‑induced changes in brain networks - Büchel, Daniel; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Scientific Reports)
Keywords: Multidisciplinary

Results of a tri-national online survey on the current status of sports injury prevention among members of the German-Speaking Orthopaedic Sports Medicine Society (GOTS) - Lutter, Christoph; Seil, R; Best, R; Gokeler, A; Patt, T; Krutsch, W; Grim, C; Tischer, T (Sportverletzung · Sportschaden)
Abstract Objectives To assess the current opinions and state of knowledge in primary sports injury prevention among members of the German-Speaking Society for Orthopaedic and Traumatologic Sports Medicine (GOTS). Methods On 21 August 2019, a web-based questionnaire was sent to the members of the tri-national society GOTS (Austria, Germany and Switzerland). The survey was online until 21 November 2019 and included twenty-two questions, which were divided into five sections: 1) general importance of prevention (n = 4), 2) specifications of the study population (n = 3), 3) implementation of prevention (n = 8), 4) improvement opportunities in prevention (n = 4) and 5) future research areas (n = 3). Results A total of 272 participants completed the survey, representing a total survey participation of 17.7 % of all members. The study population consisted of orthopaedic surgeons (55 % with surgical and 21 % with non-operative orientation), medical students (10 %), physical therapists (8 %) and sports scientists (4 %). Ninety-four percent of all participants stated that they considered the importance of sports injury prevention to be “very high” (68 %) or “high” (26 %). However, almost 70 % of all participants stated that they spend less than one hour per week on injury prevention work. The term “prevention” was clearly defined and practicable for only 40 %, understandable but difficult to implement for 51 %, and unclear and difficult to implement for 9 % of the participants. Seventy-two percent of respondents were aware of existing prevention programs such as “Stop-X” or “FIFA 11 +”, whereas 28 % of participants were uninformed regarding these programs. Conclusions A strong divergence was identified between participants’ perception of the importance of sports injury prevention and the existing implementation of preventive measures. Future funding of prevention programs, expansion of research strategies for injury prevention and better financial reimbursement are of utmost importance.